Prevalence and Antibiotic Resistance Patterns of Uropathogenic Escherichia coli Isolated from Community-Acquired Urinary Tract Infections: A Cross-Sectional Study: Uropathogenic E. coli in Community UTIs: Prevalence and Resistance - Farooq, Shomaila; Ullah, Habib; Jichao, Zhang (DEVELOPMENTAL MEDICO-LIFE-SCIENCES, 2025)
Background: Escherichia coli is the main cause of urinary tract infections (UTIs), which are among the most common community-acquired diseases in the world. Particularly in low- and middle-income nations, the growing antibiotic resistance in uropathogenic E. coli (UPEC) has become a serious therapeutic issue. Objective: To determine the prevalence and antibiotic resistance patterns of UPEC isolated from community-acquired UTIs in Pakistan. Methods: From March 2024 to April 2025, this cross-sectional descriptive research was conducted in tertiary care facilities across Pakistan. 110 midstream urine samples from people with UTI symptoms were collected in total. UPEC was grown and identified using standard microbiological techniques, and the Kirby-Bauer disk diffusion method was used to test for antibiotic susceptibility in compliance with CLSI 2023 criteria. Resistance to at least three antibiotic classes was referred to as multidrug resistance (MDR). SPSS version 25 was utilized to analyze the data. Results: UPEC was isolated in 68 of 110 urine samples, yielding a prevalence of 61.8%. The majority of cases occurred in females (72.1%), particularly in the 18–40 years age group (55.9%). Resistance was highest against ampicillin (85.3%), trimethoprim–sulfamethoxazole (73.5%), ciprofloxacin (66.2%), and levofloxacin (61.8%). Moderate resistance was noted to ceftriaxone (50.0%) and cefotaxime (48.5%), whereas aminoglycosides retained better activity, with gentamicin (39.7%) and amikacin (17.6%) showing lower resistance. Nitrofurantoin (14.7%) and fosfomycin (11.8%) were the most effective oral options, while carbapenem resistance was minimal (2.9%). MDR was detected in 51.5% of isolates. Conclusion: UPEC is the predominant cause of community-acquired UTIs in Pakistan, with high resistance to commonly prescribed agents and significant multidrug resistance. Nitrofurantoin and fosfomycin remain reliable first-line therapies, while carbapenems should be preserved for complicated cases.